Necesidad que la ley para el control y prevencion de la contaminación ambiental incorpore a su normativa la contaminacion geoambiental o tambien contaminación invisible, generada por tóxicos ambientales, contaminación electromagnética procedente de la telefonia movil y la electrificaciòn en los hogares - Alvarado Escobar, Silvia Verónica (2015)
At the present time due to technological advances we are subjected to the most usual for this type of electromagnetic emissions in our daily activities; from microwave ovens virtually every home in the world's societies considered advanced, considered to the least developed and low-income people have mobile phones or cell commonly referred to, and in the poorest households are radios, television, video and wireless internet (wifi), whose electromagnetic technology base is being questioned by the scientific community about the risks to health and the environment considered inevitable part of technological development, which have become essential tools in development daily activities of people. It is very easy to realize that we live in the midst of electromagnetic pollution from technology today surrounds the human being that is caused directly or indirectly from health problems and various conditions that today we can not have a reliable medical explanation; always it argues that suffers from electromagnetic stress to refer to the imbalance and detrimental alteration in the various vital functions of the human being from the contact or exposure to this type of radiation bulbs in each household. However, the levels of emissions that lead to the phenomenon of over-exposure or overexposure mainly to healthy individuals and all age 7 ranges, using different technological means that every time you use them emit radiation which involves directly to the means of telecommunications; but on the other hand, it is obvious that they are too many and too powerful vested interests in a technological society in which electromagnetic waves move the powerful industry of telecom operators and other multinationals. Due to ignorance of the users of new technologies and the shadow of certain lobbies or pressure groups a sensitive issue involving the health of millions of people interested in new technologies that emit non-ionizing radiation looms; we must take into account the damage caused to human health by electro smog, much of the harmful effects of electromagnetic pollution forwards and disappear shortly to let people be exposed to radiation; Despite this limited temporary effect of this contamination is not entirely weighted side effect that may result in the health of our children and the chronically ill, especially patients with certain cardiovascular diseases, epilepsy, and other ailments. Of concern is the consumer telephone service between youth and population still infant in our day, which happens to be one of the groups most at risk of impairment as a result of receiving radiation consistently and constantly, even at small doses and this at increasingly early ages seven or eight years; little is known or unknown, that there are serious and alarming suspicions, the root cause of some types of own cancer of advanced societies, advancing at the same pace as society of technology and market growth of telecommunications, as certain types of immune system disorders, leukemias, brain tumors aplasias or for which medical science finds no plausible explanation but at the same time multiply-called developed societies disorders attention deficit hyperactivity disorder in children and adolescents due to abuse of cell phones, displays, radio and television and other technological innovations as well as episodes of irritability and fatigue, anxiety and chronic headaches that some doctors relate them to be due to exposure to the technology which it is exposed. We must be aware that in our environment we are constantly subjected to a number of agents at very low doses so that its effect is imperceptible to our senses but they have a cumulative effect and ultimately damage our health, it is what we call invisible pollution that do not It is neither more nor less than the geoenvironmental, light pollution is that these terms in our environment are new and unknown however we are in the middle or are part of them. But we must be sure we are surrounded by environmental toxins, electromagnetic pollution, emissions from mobile telephony and electrification of our homes and cities, this contamination although satisfying the limits set by the authorities would still not cause us an effect in the body and ultimately can bring us health problems, moreover the place where we rest may be affected by natural radiation caused by geophysical place, variations in Earth's magnetic or electric field, which are natural agents that have a negative effect on our health.